Effects of Retro-Walking on Pain, Functional Disability and Performance in Knee Osteoarthritis - Shabbir, Saira; Hashim, M.; Sajjad, Raneem; Kayani, Maliha S; Syed, Fizza A.; Ibrahim, Mubashra; Hassan, Danish; Ghouri, M. Hashim (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Osteoarthritis is a degenerative disease, considered common cause of disability. Treatment options include pharmacological interventions, joint cavity injections, physical exercises and joint replacement surgeries. Aim: To determine effects of combined retro-walking and conventional therapy on pain, functional disability and performance in knee osteoarthritis. Method: Randomized controlled trial conducted at Max Rehab Physiotherapy Department. 36 patients meeting criteria randomly allocated into two groups through random number allocation method. Experimental group treated with Retro-walking with conventional therapy; duration of the session was 30 minutes, three days a week for 6 weeks. Control group received conventional therapy alone for period of 30 minute; 1 set of 10 repetitions twice for 1.5 months, Pre-assessment and post-assessment evaluated through NPRS, WOMAC & TUG. Data analyzed using SPSS 21. Results: Experimental group had significant decrease in pain intensity level and functional disability than control group i.e. p = 0.000. Experimental group showed improvement in timed up and go test i.e, p = 0.000. Analysis of experimental group versus control group revealed significant difference in reducing pain (p< 0.001). Differences in rest of outcome variables were not significant (p>0.001). Conclusion: Combination of retro walking along with conventional therapy is useful to improve pain, functional disability in patients suffering from knee osteoarthritis.